Extreme programming method in the design of e-ticket information system for roro bengkalis port web-based - Abu Hurairah; Mentari Tri Indah Rahmayani (Institute of Computer Science (IOCS), 2023)
Extreme programming method in the design of e-ticket information system for roro bengkalis port web-based